Fracture resistance of CAD/CAM milled versus direct hand-made interim laminate veneers - Salahaldeen Abuhammoud; Banan Emtier; Chin-Chuan Fu; Silvia Rojas-Rueda; Carlos A. Jurado; Kelvin I. Afrashtehfar (Elsevier, 2024)
Background: Comparative studies of interim veneer restorations crafted using subtractive computer-aided manufacturing (s-CAM) milling technology and traditional direct hand-made approaches are needed. Purpose: This comparative in vitro study evaluated the fracture resistance of two types of provisional veneer restorations for maxillary central incisors: milled (s-CAM) and traditional direct hand-made bis-acryl veneers. Materials and methods: Fifty maxillary right central incisor veneers (25 specimens per group) were fabricated and divided according to the fabrication method: (1) s-CAM milled (Structure CAD, VOCO Dental); and (2) hand-made (Protemp Plus, 3M). The restorations were cemented onto 3D-printed resin dies using temporary cement and subjected to 1000 cycles of thermal cycling between 5° and 55 °C. These restorations subsequently were subjected to compressive loading until fracture occurred. Images of the fractured samples were captured using a scanning electron microscope (SEM). Statistical analysis was performed using the one-way ANOVA test and the Mann-Whitney U test. Results: Significant differences (p < 0.001) in the fracture resistance were observed between the two groups. s-CAM milled interim veneers displayed higher fracture resistance values (439.60 ± 26 N) compared to the traditional method (149.15 ± 10 N). Conclusion: The manufacturing method significantly influences the fracture resistance of interim veneer restorations. s-CAM interim laminate veneer restorations for maxillary central incisors exhibit a fracture resistance superior to that of the traditional method using bis-acryl.Clinical relevanceClinicians should consider CAD/CAM milled veneers for scenarios demanding long-term interim restoration and the withstanding of high occlusal forces.